2012
DOI: 10.1002/hyp.9602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of runoff characteristics of two adjacent basins in a tropical rainforest using a modified hydrologic cycle model with outflow

Abstract: Abstract:We propose a new runoff model including an outflow process that was applied to two adjacent basins (CL, TL) located in Lambir Hills National Park in north-central Sarawak, Malaysia. Rainfall, runoff, topography, and soil layer thickness were observed. About 19% of annual runoff was observed in the CL basin (21.97 ha), whereas about 46% was observed in the TL basin (23.25 ha). It was inferred that the CL basin has an outflow because of low base flow, small runoff peak, and excessive water loss. By inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this study, we used the HYCY model (Fukushima, 1988) by incorporating the outflow factor proposed by Wakahara et al (2014) to estimate outflow such as groundwater flow into bedrock or other watersheds. The outflow component representing the bedrock groundwater infiltration was attached to the base flow tank and was calculated by multiplying the outflow ratio and the base flow rate under the assumption that bedrock infiltration mainly occurs through the stream bed.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the HYCY model (Fukushima, 1988) by incorporating the outflow factor proposed by Wakahara et al (2014) to estimate outflow such as groundwater flow into bedrock or other watersheds. The outflow component representing the bedrock groundwater infiltration was attached to the base flow tank and was calculated by multiplying the outflow ratio and the base flow rate under the assumption that bedrock infiltration mainly occurs through the stream bed.…”
Section: Site Descriptionmentioning
confidence: 99%
“…They observed that the base flow rate could be determined by groundwater flow through bedrock and inter-catchment groundwater transfer in second-and third-order catchments. Further, Wakahara et al (2014) modified the hydrological cycle (HYCY) model (Fukushima, 1988) to quantify outflow from catchments in the form of deep infiltration or lateral flow and demonstrated that low base flow was caused by outflow escaping from the basin. Kosugi et al (2006) directly measured bedrock infiltration.…”
Section: Introductionmentioning
confidence: 99%